2006
DOI: 10.1523/jneurosci.0808-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Automatic and Strategic Lexical-Semantics: Functional Magnetic Resonance Imaging Evidence for Differing Roles of Multiple Frontotemporal Regions

Abstract: Behavioral research has demonstrated three major components of the lexical-semantic processing system: automatic activation of semantic representations, strategic retrieval of semantic representations, and inhibition of competitors. However, these component processes are inherently conflated in explicit lexical-semantic decision tasks typically used in functional magnetic resonance imaging (fMRI) research. Here, we combine the logic of behavioral priming studies and the neurophysiological phenomenon of fMRI pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
245
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(287 citation statements)
references
References 62 publications
40
245
2
Order By: Relevance
“…Many studies have found priming related decreases in the same regions as shown in our studies, however, some studies have shown semantic priming related increases in activity (e.g.. Rossell et al, 2003;Kotz et al, 2002). As was found in our study, the majority of semantic priming studies have found semantic priming related reductions in at least some portion of the middle temporal gyrus (Copeland et al, 2003;Giesbrecht et al, 2004;Rissman et al, 2003;Rossell et al, 2003;Kotz et al, 2002 andGold et al, 2006) and of the inferior frontal region (Copeland et al, 2003;Giesbrecht et al, 2004;Kotz et al, 2002;Matsumo et al, 2005;Wheatley et al, 2005). In fact, the one region that showed activity related to both long and short SOA priming in Gold et al, (a portion of the posterior middle temporal gyrus) was neuranatomically very close to the region showing correlations with thought disorder in the current study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Many studies have found priming related decreases in the same regions as shown in our studies, however, some studies have shown semantic priming related increases in activity (e.g.. Rossell et al, 2003;Kotz et al, 2002). As was found in our study, the majority of semantic priming studies have found semantic priming related reductions in at least some portion of the middle temporal gyrus (Copeland et al, 2003;Giesbrecht et al, 2004;Rissman et al, 2003;Rossell et al, 2003;Kotz et al, 2002 andGold et al, 2006) and of the inferior frontal region (Copeland et al, 2003;Giesbrecht et al, 2004;Kotz et al, 2002;Matsumo et al, 2005;Wheatley et al, 2005). In fact, the one region that showed activity related to both long and short SOA priming in Gold et al, (a portion of the posterior middle temporal gyrus) was neuranatomically very close to the region showing correlations with thought disorder in the current study.…”
Section: Discussionsupporting
confidence: 80%
“…However, a number of other regions not found in the current study were also described to have shown priming effects in some studies. These include the superior temporal gyrus (Rissman et al, 2003;Kotz et al, 2002;Matsumo et al, 2005) and the posterior fusiform gyrus in studies using visual words (Wheatley et al, 2005;Gold et al, 2006). Schizophrenic subjects displayed less clear within-group activation reductions in response to word pair connectivity in left frontal and temporal regions.…”
Section: Discussionmentioning
confidence: 99%
“…fMRI data was analyzed with AFNI software (Cox, 1996) using a series of steps similar to those in Gold et al (2006). Preprocessing of the fMRI data included the following steps.…”
Section: Analysis Of Fmri Datamentioning
confidence: 99%
“…The directions were (x, y, z) = (0, 0, 0), (1, 1, 0), (1, -1, 0), (1, 0, 1), (1, 0, -1), (0, 1, 1), (0, 1, -1), where 1 indicates a gradient applied in that direction (Basser and Pierpaoli, 1996). During the same scanning session, participants also took part in a separate fMRI experiment (in which four gradient-echo EPI runs were also acquired) as part of a primed lexical decision study that has been reported elsewhere (Gold et al, 2006).…”
Section: Mri Acquisitionmentioning
confidence: 99%